Laboratory Head Strategy in Improving Laboratory Management Effectiveness in Junior High Schools - Luma, Sarwendah C.; Lengkong, Jeffry SJ; Usoh, Elni J. (Yayasan Abdurrauf Cendekia Nusantara, 2025)
The objectives of this study are (1) To analyze the strategies implemented by the Head of Laboratory in improving the effectiveness of laboratory management at State Junior High School 3 Belang. (2) To investigate the factors that influence the success of implementing the strategy. (3) To describe the impact of the strategies implemented on the quality of student learning at State Junior High School 3 Belang. The research method used is qualitative. Data collection techniques using interviews, observations, and documentation. The data analysis technique in this study uses data analysis techniques in the field of data reduction, with the process of data reduction and presentation. The results of this study are (1) The strategy of the head of the laboratory in improving the effectiveness of laboratory management at State Junior High School 3 Belang must include several main things, namely, mature planning and management, training and development of Human Resource competencies, utilization of information technology, security and safety in the use of the laboratory, and building internal and external collaboration, all of which are still not optimal. (2) Factors that influence the success of implementing the laboratory head's strategy in improving the effectiveness of laboratory management at State Junior High School 3 Belang are the competence of laboratory staff and technicians, support from the school, and good coordination with subject teachers and laboratory staff. (3) The impact of the strategy implemented on the quality of student learning at State Junior High School 3 Belang is that students become enthusiastic about learning when learning is carried out in the laboratory and students become more active and teachers are more assisted in teaching.